TINGKAT KECEMASAN REMAJA PUTRI DI SMA MUHAMMADIYAH I PARE DALAM MENGHADAPI HAID - Slamet, Eko; Cahyono, Aris Dwi; Purwati, Purwati (Akademi Keperawatan Pamenang, 2010)
Anxiety is an situation jiggling caused by threat to health, particularly to is adolescent of woman whichnot yet comprehended correctness about menstruation, menstruation which is not regular to be accompaniedpain in bone often generate panicity andanxiety at adolescent, intention of this research is to know adolescentanxiety level of woman in SMA Muhammadiyah I Pare facing menstruation.In this research the used is descriptive desain, its population all is adolescent of women in l SMAMuhammadiyah I Pare, by using technique total sampling, with amount of sampel 83 responder.From result ofresearch got at most natural responder of anxiety that is 36 responder (43,4%), hereinafter 32 responder(38,6%) experiencing of light anxiety, 9 responder (10,8%) experiencing of heavy anxiety, and at least 6responder (7,2%) do not experience of anxiety.According to breakdown of above showing at most natural responder of anxiety, this matter is enabledbecause pertained age factor is adolescent age, besides type of stressor also very is influencing anxiety level. Seeresult of the research according to researcher need the existence of counseling about woman reproductionspecially regarding menstruate to add knowledge and information so that can lessen anxiety.